2012
DOI: 10.1371/journal.pone.0044095
|View full text |Cite
|
Sign up to set email alerts
|

Novel Direct Targets of miR-19a Identified in Breast Cancer Cells by a Quantitative Proteomic Approach

Abstract: The miR-17–92 cluster encodes 7 miRNAs inside a single polycistronic transcript, and is known as a group of oncogenic miRNAs that contribute to tumorigenesis in several cancers. However, their direct targets remain unclear, and it has been suggested that a single miRNA is capable of reducing the production of hundreds of proteins. The majority of reports on the identification of miRNA targets are based on computational approaches or the detection of altered mRNA levels, despite the fact that most miRNAs are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…Identification of cancerspecific miRNAs as well as their target genes is important for elucidating the roles of miRNAs in tumorigenesis and may provide promising therapeutic targets. In this study, we focused on miR-19a, which has been suggested to promote tumor growth in several human cancers, such as breast cancer (Ouchida et al, 2012), multiple myeloma (Pichiorri et al, 2008), cervical cancer (Xu et al, 2012) and B-cell lymphomas (Liu et al, 2011). Recently, Ueda and colleagues found that miR-19a were upregulated in gastric cancer tissues, and overexpression of miR-19a was also associated with progression and prognosis of gastric cancer (Ueda et al, 2010), yet the detailed mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of cancerspecific miRNAs as well as their target genes is important for elucidating the roles of miRNAs in tumorigenesis and may provide promising therapeutic targets. In this study, we focused on miR-19a, which has been suggested to promote tumor growth in several human cancers, such as breast cancer (Ouchida et al, 2012), multiple myeloma (Pichiorri et al, 2008), cervical cancer (Xu et al, 2012) and B-cell lymphomas (Liu et al, 2011). Recently, Ueda and colleagues found that miR-19a were upregulated in gastric cancer tissues, and overexpression of miR-19a was also associated with progression and prognosis of gastric cancer (Ueda et al, 2010), yet the detailed mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Further, E2F transcription factors can regulate miR-17-92 cluster [56,57], indicating the circulating feedback regulation between these genes. miR-19a has been reported to regulate a variety of biological processes, including spinocerebellar ataxi [30], multiple myeloma [31], and breast cancer [32]. However, its role in inflammation especially in IBD is rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the biology of multiple myeloma, miR-19a is shown to downregulate the expression of SOCS-1 [31]. In breast cancer, four upregulated proteins, PPP2R2A, ARH-GAP1, IMPDH1 and NPEPL1, were shown to have miR-19a binding sites on their mRNAs using quantitative proteomic approach [32]. Other miR-19a targets are predicted using a HeLa cell reporter system, including Bim [33].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the down-regulation of miR-92a in plasma also correlated with response to treatment. Unfortunately, limited information is available describing the function of miR-19a, the only available information identifies it as up-regulated in many cancers 5153 . Interestingly, Yu et al showed that over-expression of miR-19a suppressed CD142 expression and inhibited cell migration and invasion in colon cancer 53 .…”
Section: Discussionmentioning
confidence: 99%